Influencia de la concentración del ácido cítrico y pH en la lixiviación de copelas usadas, la densidad de corriente y distancia de electrodos en la electrodeposición del plomo lixiviado - Rivera Blas, Iván Ricardo (2016)
This study aimed to investigate the influence of the concentration of citric acid and pH in the leaching of crucibles used, current density and electrode distance in the electrodeposition of leached lead, the parameters used thereby managed to get a high percentage extraction were: 1M citric acid concentration, pH 5, current density 90 A / m2 and 1cm electrode distance; each test was performed with 5 g of sample, -140 mesh particle size, stirring speed of 220 rpm, stirring time of 2 hours, 200 mL of leaching solution, electrolysis time of 1 hour at ambient conditions, these parameters mentioned generated as optimum results in a 96.40%, this research work has four variables with three levels each, citric acid concentration: 0.2, 0.5, 1M; pH: 4, 5, 6; current density: 30, 60, 90 A / m2; and electrode distance: 1, 2, 3 cm; after comparing the results obtained in the analysis of variance, with a confidence level of 95%, it showed that the four variables have a significant impact study and their interactions also have significant difference on the lead extraction